Anaerobic Soccer Training Model: Enhancing Soccer Players’ Performance through a Combination of Repeated Sprints and 4 vs 4 Games - I Dewa Made Aryananda Wijaya Kusuma; Nining Widyah Kusnanik; Bayu Agung Pramono; Adi Pranoto; Yanyong Phanpheng; Indra Himawan Susanto; Dewa Ayu Praba Amustikarani; Waristra Tyo Nirwansyah; Muhammad Bagus Firzam Bharlaman (Physical Education Theory and Methodology)
Objectives. The Anaerobic Soccer Training (AnST) model was designed to increase variation in soccer training programs by implementing a game-based approach to matching characteristics. This study aimed to evaluate the effectiveness of the training model in improving soccer players’ anaerobic abilities.